Master’s Students in History Could Benefit from a Greater Library Sensitivity and Commitment to Interdisciplinarity, and from More Efficient Document Delivery - Hunsucker, R. Laval (Evidence Based Library and Information Practice, 2011)
Objective – This study sought to determine the characteristics of research materials used by history students in preparing their master’s theses. Of which information resources formats did such students make use, and in what proportions? What was the age distribution of resources used? What was the dispersal over journal titles and over subject classification, i.e., the degree of interdisciplinarity? To what extent did the master’s students make use of non-English-language materials? To what extent did their institution’s library hold the resources in question? The investigator was especially interested in finding quantitative support for what he terms two “hypotheses.” The first of these is that historical research depends to a high degree on monographs, journal articles being far less important to it than they are to research in, especially, the natural sciences and technology. The second is that the age distribution of resources important to historical research is much flatter and longer than that of resources upon which researchers in the natural sciences and technology rely. Design – Citation analysis, supplemented with comprehensive catalogue searches. Setting – Southern Connecticut State University (SCSU), a mid-sized public university located in New Haven, Connecticut, U.S.A. Subjects – MA and MS theses (N=47) successfully submitted to the Department of History over the period from academic year 1998/1999 through academic year 2007/2008, inclusive. Methods – The investigator initially identified the theses through a search of the online catalogue (“Consuls”) of the Connecticut State University system, and retrieved all of them in either electronic or hard-copy form. He then subjected all citations (N=3,498) listed in the references sections of these theses to an examination in order to identify for each cited resource the format, the age, the language, and, in the case of scholarly journal articles, the journal of publication. He carried out bibliographic searches in order to rectify any citations which he had noted to be faulty or incomplete. The study took no account of possible additional citations in footnotes or endnotes or in the text, and did not measure citation intensity (whether, for instance, a thesis referred only once, or perhaps many times, to a given resource). Duplicates “were ignored.” He furthermore performed systematic searches in Consuls and in the Library of Congress (LC) online catalogue in order to establish, insofar as possible, into which assigned LC Classification class each resource fell, and whether it belonged to the holdings of the SCSU library. “Holdings,” as used here, includes physical resources owned, as well as those resources to which the library has licensed access. Not marked as either “held” or “not held” were: resources available online without restriction or charge, items not identified in either Consuls or the LC catalogue, and all government documents. Ages of cited resources were calculated based on the edition or version date actually given in a student’s citation, without any consideration of a possible earlier date of the original version of the publication or document concerned. Main Results – Format, age distribution, and journal frequency. The local citation analysis found that 53.2% of all cited resources were monographs, 7.8% were scholarly articles, 5.3% were contributed chapters in books, and 0.6% were dissertations or theses. Non-scholarly periodicals accounted for 15.7%, government documents for 6.7%, and freely available web documents for 4.1%. The remainder, approximately 6.5%, comprised archival papers, judicial documents, directories, interviews, posters, audiovisual materials, and 13 other formats. Cited resources, measured back from the date of acceptance of the citing thesis, ranged from 0 to 479 years old; the mode was 3 years, but the median was “25” (p. 170) or “26” (p. 177) years. Just over 70% (i.e., 2,500 cited resources) were more than ten years old. Almost one thousand of the cited resources were fifty or more years old. The 274 scholarly journal articles included in the references sections were spread over 153 distinct journal titles, of which 105 titles made only one appearance, and 136 titles three or fewer appearances. The mean was 1.8 appearances. Subject dispersal and language. Of the 2,084 cited resources for which LC classification was locatable, 51.5% had a classification other than history, i.e., other than class C, D, E, or F. Nearly two thirds (66.0%) of the cited scholarly journal articles had appeared in journals with a focus other than history. (Note: table 4 is incorrect, precisely reversing the actual ratio.) Of all cited items, 98.5% were in the English language. Half (27) of the non-English-language resources cited were in Korean, all cited in the same thesis. Books (i.e., monographs plus compilations from which contributed chapters were cited) accounted for 87.0% of foreign-language citations. More than four fifths of the examined theses (83.0%) cited not a single non-English-language resource. Local holdings. Of all 3,498 cited items, 3,022 could be coded as either “held” or “not held” by the SCSU library. Of the items so coded (not, as indicated on p. 180, of all cited items), scarcely two fifths (41.0%) belonged to the library’s holdings. The holdings percentage was highest (72.6%) for the 274 scholarly journal articles cited, followed by the 186 contributed chapters (50.0%), the 550 non-scholarly periodical items (49.5%), and the 1,861 monographs (46.8%). For other cited formats, the percentage was much lower, and in some cases, e.g., for the 55 archival and the 44 judicial documents, it was 0.0%. Of the 54 foreign-language resources cited, the institution’s library held only two. Conclusion – The investigator concludes that his study’s findings do indeed lend quantitative support to his two “hypotheses.” This outcome will surprise few, if any, librarians; it is in accord with what Koenig (1978) long ago saw as a matter of “intuition” and “all conventional wisdom,” something that many subsequent studies have confirmed. Sherriff accordingly recommends, firstly, that collections which strive to support historical research should, in matters of acquisition policy and budget allocation, take serious account of that field’s relatively strong dependence on monographs. Secondly, the data on age distribution carry obvious implications for librarians’ decision-making on matters such as de-accessioning and weeding, relegation to remote storage, and retrospective acquisitions. This finding should also be considered, for instance, in connection with preservation policy and the maintaining of special collections. He even suggests that librarians “need to teach students the value of reviewing literature historically and showing them how to do so effectively” (p. 177). Sherriff considers a number of further (tentative) conclusions to be warranted or suggested by the results of this study. First of all, that historical research is now characteristically an interdisciplinary matter, in the sense that it requires extensive access to information resources, including journals, which libraries have traditionally not classified as belonging to the discipline of history itself. For a library supporting such research, this phenomenon “has implications for matters including collection budgets, reference work, bibliographic instruction, and the location of collections and departmental libraries” (p. 168). It also means “that librarians working with history students and history collections need to be aware of the relevant resources in other disciplines. This can improve reference work, research assistance, and bibliographic instruction; it may also help the coordination of acquisitions across departmental lines” (p. 179). Secondly, one may conclude that “there is no ‘core’ collection of journals for history” (p. 178) which will be able to satisfy a large proportion of master’s students’ research needs. Thirdly, the fact that a library such as SCSU’s holds significantly less than half of what master’s students require for preparing their theses “may exercise a narrowing effect on students’ awareness of the existing literature on their topics” (p. 180), “increases the importance of departmental faculty, reference librarians, and subject specialist librarians drawing students’ attention to resources beyond the library’s catalogues and collections” (p. 180), and requires that the library give serious attention to effective document delivery arrangements. Finally, this study’s finding that only a small percentage of master’s students in history made use of non-English-language materials, but then in certain cases used them rather extensively (27 Korean items cited in one thesis, ten Italian in another, nine Spanish in yet another), suggests that acquisition, or at least proactive acquisition, of such materials needn’t be a priority, as long as, once again, the students concerned have easy access to efficient and affordable document delivery services. Sherriff does concede, however, that his finding could indicate “that students are unaware of relevant resources in other languages or are aware of them but lack the language skills necessary to use them” (p. 179).